Evolution of pegmatite ore-forming fluid: The Lijiagou spodumene pegmatites in the Songpan-Garze Fold Belt, southwestern Sichuan province, China - Fei, Guangchun; Menuge, Julian F; Chen, Changsheng; Yang, Yulong; Deng, Yun; Li, Youguo; Zheng, Luo (Ore geology reviews, 2021)
[Display omitted] •Lijiagou spodumene pegmatites formed from high temperature, low salinity, volatile-enriched magmatic fluids.•Lithium enrichment occurred during fluid immiscibility.•The Lijiagou spodumene pegmatites have no direct magmatic relationship with any of the Ke'eryin plutonic rocks. The late to post-tectonic Lijiagou spodumene pegmatites are located in the Ke’eryin orefield, which lies in the Triassic central Songpan-Garze Fold Belt (SGFB) in southwestern Sichuan Province, China. Fluid inclusion petrography, microthermometry and Raman spectroscopic analyses were carried out on quartz and spodumene in granites and four types of pegmatite in the Ke’eryin orefield. A Hydrothermal Diamond Anvil Cell (HDAC) was used to observe the microthermometric behavior of crystal-rich inclusions. Five types of fluid inclusions were identified. Crystal-rich inclusions (Type 1) in spodumene pegmatites were trapped at high temperature (658 to 741 °C) and high pressure (>4.7 kbar). Other inclusion types were found in granite and all types of pegmatite. Triphase CO2-H2O (CO2 + V + L, Type 2) inclusions show medium homogenization temperatures (324 to 339 °C), medium trapping pressures (2.09 to 2.54 kbar) and low to moderate salinities (3.1 to 11.3 wt% NaCl equiv). Biphase aqueous inclusions (L + V, Type 3) show similar homogenization temperatures (319 to 347 °C), and low to moderate salinities (5.5 to 18.0 wt% NaCl equiv). Monophase liquid CO2 (Type 4) inclusions have very low homogenization temperatures (15.4 to 19.1 °C). Monophase liquid H2O (Type 5) inclusions have moderate ice melting temperatures (–18.6 to –9.8 °C), and moderate salinities (18.4 to 18.5 wt% NaCl equiv). The various types of fluid inclusion reveal the P–T conditions of pegmatite formation, which records the transition from a magmatic to a hydrothermal environment and indicate that the ore-forming fluid resulted from the unmixing of magmatic melt. Fluid immiscibility is the key mechanism responsible for formation of the Lijiagou spodumene pegmatites and lithium mineral precipitation occurred from a high to medium temperature CO2-rich fluid. The absence of temperature and salinity gradients between granite and progressively more distal and evolved pegmatite compositions is inconsistent with formation of pegmatite magmas by fractional crystallization of granitic magmas, but consistent with separate anatectic origins of each type of pegmatite magma.